Investigating sine-band hysteresis control of photovoltaic-grid connected inverter - M. Della Krachai; K. Melouk; M. Keddar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
In this paper, an optimization of PV grid connected system is investigated. This is achieved by considering the application of artificial intelligence in the DC side to realize maximal power extraction, and using a sine-band hysteresis control in the AC side of the system, to generate a sine current/voltage suitable for grid connection IEEE929-2000 standards. The overall system has been simulated taking into account environmental effects and standards constraints in order to achieve best performance. The choice of sine band hysteresis control was selected considering its implementation simplicity. The algorithm runs fast on a low-cost microcontroller allowing to avoid any delay that can cause a phase shift in the system.  An experimental setup has been realized for tests and validation purposes. Both simulation and experimental results lead to satisfactory results which are conform to the IEEE929-2000 standards.